Comparison of non-criteria antiphospholipid syndrome with definite antiphospholipid syndrome: A systematic review - Pires da Rosa, Gilberto; Ferreira, Ester; Sousa-Pinto, Bernardo; Rodríguez-Pintó, Ignasi; Brito, Iva; Mota, Alberto; Cervera, Ricard; Espinosa, Gerard (Frontiers in Immunology, 2022)
Objectives. Patients with laboratory or clinical manifestations suggestive of antiphospholipid syndrome (APS) but not fulfilling the classification criteria constitute a clinical challenge. This study aims to compare non-criteria APS (NC-APS) with definite APS in terms of clinical manifestations, therapies, and outcomes. Methods. A systematic review of observational studies comparing definite and NC-APS was performed searching four electronic databases. Data on clinical manifestations, therapies and clinical outcomes was extracted. Results. Sixteen studies, assessing a total of 3,798 participants, were included. Seven out of 10 studies found no significant difference in the prevalence of arterial or venous thrombosis between definite and NC-APS, with two studies on seronegative APS also finding no difference in thrombosis recurrence. Seven out of 12 studies found no significant difference in the prevalence of obstetric manifestations between groups, with the remaining exhibiting conflicting results. In 9 studies comparing treatment frequency in obstetric patients, all but one described similar treatment frequency, with the percentage of NC-APS treated during pregnancy ranging from 26% to 100%. In 10 studies comparing pregnancy outcomes of NC-APS versus definite APS, 7 found similar successful pregnancies/live births. Additionally, 5 studies described improvement of live births in both groups with treatment, with three signalling aspirin monotherapy as efficacious as combination therapy in NC-APS. Conclusion. This review hints at an absence of marked differences in most evaluated parameters between definite and NC-APS, emphasizing the value of a more active follow-up of these patients. The low-quality available evidence highlights the need for well-defined NC-APS populations in future studies.